2008
DOI: 10.1200/jco.2007.15.0185
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Study, V-15-32, of Gefitinib Versus Docetaxel in Previously Treated Japanese Patients With Non–Small-Cell Lung Cancer

Abstract: Noninferiority in overall survival between gefitinib and docetaxel was not demonstrated according to predefined criteria; however, there was no statistically significant difference in overall survival. Secondary end points showed similar or superior efficacy for gefitinib compared with docetaxel. Gefitinib remains an effective treatment option for previously treated Japanese patients with NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
256
5
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(274 citation statements)
references
References 17 publications
12
256
5
1
Order By: Relevance
“…In addition, once the patients are diagnosed as not harboring sensitive EGFR mutations, physicians might not treat them with EGFR-TKIs even after the relapse of first-line chemotherapy, though second-line gefitinib was previously reported to show acceptable toxicity and efficacy for patients with NSCLC harboring EGFR-sensitive mutations. 27,28 Thus, a false negative seems to be a more severe problem for patients with NSCLC harboring EGFR-sensitive mutations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, once the patients are diagnosed as not harboring sensitive EGFR mutations, physicians might not treat them with EGFR-TKIs even after the relapse of first-line chemotherapy, though second-line gefitinib was previously reported to show acceptable toxicity and efficacy for patients with NSCLC harboring EGFR-sensitive mutations. 27,28 Thus, a false negative seems to be a more severe problem for patients with NSCLC harboring EGFR-sensitive mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Although several phase 3 studies comparing EGFR TKIs with chemotherapy in the second-line setting have demonstrated that similar efficacy exists between EGFR TKIs and chemotherapy, to the best of our knowledge these studies were not designed to investigate the potential effect of EGFR mutational status on efficacy. 8,9,16,[20][21][22] The TAILOR (TArceva Italian Lung Optimization tRial) trial compared erlotinib with docetaxel as the second-line treatment of advanced NSCLC in patients with wild-type EGFR disease. Results of the trial demonstrated that compared with docetaxel, erlotinib was effective in patients with wild-type EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…The National Cancer Institute of Canada Clinical Trials Group Study BR.21 trial reported prolonged survival with erlotinib compared with placebo (median survival, 7.9 months vs 3.7 months) in patients with advanced non-small cell lung cancer (NSCLC) after the failure of previous chemotherapy, 7 whereas in the INTEREST (IRESSA Non-small-cell lung cancer Trial Evaluating REsponse and Survival against Taxotere) study and the V-15-32 study, gefitinib was found to have noninferior survival compared with docetaxel. 8,9 Several studies have demonstrated that a high EGFR gene copy number was associated with great sensitivity and prolonged progression-free survival (PFS) among patients with NSCLC after treatment with EGFR TKIs. 7,[10][11][12][13][14] However, subsequent studies indicated that a high EGFR copy number was not associated with greater PFS when comparing EGFR TKIs versus chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we evaluated the prognosis of elderly patients with NSCLC treated with second-line chemotherapy. The previous trials of docetaxel as second-line chemotherapy in younger patients with NSCLC showed that median PFS and OS were 2.8-3.2 months and 6.0-14.8 months, respectively [8][9][10][11][12][13][14][15]. In this study, there was no statistically significant difference in PFS and OS at the second-line chemotherapy between the age ≥ 75 group and the age 70-74 group.…”
Section: Discussionmentioning
confidence: 36%
“…ORR of the second-line chemotherapy was 9.2% [95% confidence interval (CI), [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] in age ≥ 75 group and 12.2% (95% CI, 5-26) in age 70-74 group. There was no significance difference between the groups (p=0.75).…”
Section: Efficacymentioning
confidence: 99%